E-portfolio as an academic writing assessment tool in higher education: Strengths and challenges - Wirawati Ngui; Vincent Pang; Wendy Hiew (Universitas Pendidikan Indonesia, 2022)
This study investigated the use of an e-Portfolio for assessment at a Malaysian public university. Prior to the advent of the Internet, paper portfolios are ubiquitous forms of projects and assessments. However, they have limitations in terms of portability, shareability, and delayed two-way communication between instructors and students about progress. In lieu of paper portfolio, the e-Portfolio was introduced in an advanced English language course at a public university in Malaysia. The novelty of the e-Portfolio’s implementation renders it necessary to seek the insights of those who are directly involved in its use. Therefore, this study aims to explore the perceptions of the instructors and students regarding their use of the e-Portfolio throughout the course. This is a qualitative study whereby the main data collection method involved interviews. The data were imported to NVivo 12, and thematic analysis was used as the primary method of data analysis. A total of three instructors and 18 students participated in this study. The findings reveal that the instructors and students perceived the contribution of the e-Portfolio in the aspects of writing stages, digital artefacts, accessibility, personalised writing experience, feedback and communication, and motivation. The results demonstrate that mutually perceived challenges by the instructors and students were poor Internet connectivity and difficulty adapting to the e-Portfolio. The study highlights the benefits and shortcomings of using the e-Portfolio as an assessment tool for academic writing. This will guide practitioners and researchers to better implement the e-Portfolio in higher education institutions.